(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Water is life for us, but under harsh circumstances, this water pollutes day by day. So it can be assumed that our (water) life is now not secure. We’re in a time of crisis. Water contamination is a huge concern for all across the globe. All around the planet, it impacts drinking water, ponds, reservoirs and oceans. As a consequence, it affects the well-being and wellbeing of human beings and the natural world. The present thesis seeks to address the impact of this waste on Earth, essentially what water pollution is and reflects on various sources of water pollution. Analysis has shown that water contamination not only impacts the morbidity and mortality of human life, but also the environment as a whole. Water contamination in the research region is primarily induced by overcrowding, farming activities, land degradation, industrialization and urbanization.